2019
DOI: 10.1002/ejoc.201900638
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Metal‐Free Photoinduced Preparation of Valuable 8‐Arylxanthines

Abstract: A set of 8‐arylxanthines was prepared under metal‐free conditions and in aqueous solvents from arylazo sulfones and caffeine or theophylline. Notably, the process took place by simply exposing the reaction vessel to visible or solar light, and unreacted xanthine could be easily recovered during the purification step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…In 2019, Fagnoni and co-workers established a protocol for the CÀ H arylation of xanthines with aryl azosulfones without any external photocatalyst. [52] The reaction proceeds smoothly under both sunlight (in a flow reactor) and blue light irradiation (in pyrex vessel). Mild to strong acids (HCOOH or HCl) were employed for xanthine's solubility since it precipitated during the reaction.…”
Section: Cà H Arylation Of Xanthines With Aryl Azosulfonesmentioning
confidence: 99%
“…In 2019, Fagnoni and co-workers established a protocol for the CÀ H arylation of xanthines with aryl azosulfones without any external photocatalyst. [52] The reaction proceeds smoothly under both sunlight (in a flow reactor) and blue light irradiation (in pyrex vessel). Mild to strong acids (HCOOH or HCl) were employed for xanthine's solubility since it precipitated during the reaction.…”
Section: Cà H Arylation Of Xanthines With Aryl Azosulfonesmentioning
confidence: 99%
“…The same reactions were also optimized (in three different geographical locations, Germany, Italy, and Brazil) under flow conditions by adopting a solar microcapillary reactor (the so-called “Sunflow” apparatus), a device that allowed for an efficient conversion of the substrate after only 1 h of exposition to natural sunlight. A similar approach was exploited for the direct C–H arylation of caffeine 8a and theophylline 8b in aqueous acidic media . Indeed, it was demonstrated that the biological performance of a xanthine is significantly improved by the presence of an aryl group at the 8-position (as in compound 9 , Scheme a) .…”
Section: Arylazo Sulfones In Aryl–c Bond Formationmentioning
confidence: 99%
“…A similar approach was exploited for the direct C−H arylation of caffeine 8a and theophylline 8b in aqueous acidic media. 33 Indeed, it was demonstrated that the biological performance of a xanthine is significantly improved by the presence of an aryl group at the 8-position (as in compound 9, Scheme 5a). 34 The process can be performed successfully also by using a 456 nm Kessil Lamp as the light source.…”
mentioning
confidence: 99%
“…[46] Such behavior was exploited in the development of several metal-free arylation protocols for the preparation, among the others, of aromatic stannanes, [47] phosphonates, [48] boranes, [49,50] sulfides [50] and arylated heterocycles. [51,52] We thus considered the opportunity of developing a visible light-driven procedure for the synthesis of aryl selenides and tellurides where neither catalyst nor additives were adopted (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…[ 46 ] Such behavior was exploited in the development of several metal‐free arylation protocols for the preparation, among the others, of aromatic stannanes, [ 47 ] phosphonates, [ 48 ] boranes, [ 49,50 ] sulfides [ 50 ] and arylated heterocycles. [ 51,52 ]…”
Section: Introductionmentioning
confidence: 99%